PENGARUH UKURAN DEWAN DIREKSI, DEBT RATIO, DAN UKURAN PERUSAHAAN TERHADAP KINERJA PERUSAHAAN - Biliputra, Kevin; Rasyid, Ardiansyah (Jurnal Paradigma Akuntansi, 2024)
The purpose of this research is to obtain empirical evidence about the effects of the board of directors, debt ratio, and firm size to firm’s performance of the manufacturing companies listed in the Indonesia Stock Exchange in the period of 2017-2019. This research uses 74 manufacturing companies as sample and also use multiple regression analysis. The results of this research show that debt ratio has a significant positive effect on firm’s performance while size of the board of directors and firm size has no significant effect on firm’s performance.